A DSM-5-Based Online Mental Health Referral Inventory: A Large-Scale Validation Study. Issue 3 (3rd July 2017) - Epstein, Robert; Ho, Megan; Hyun, Seojin; Le, Christopher; Robertson, Ronald E.; Stout, Dayna
ABSTRACT: In 2007, a comprehensive mental health referral inventory based on the 4th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) was posted online as an alternative to the informal tests the public now uses to self-diagnose mental health problems. A validation study was published in 2011 (Epstein & Muzzatti, 2011 ). In 2013, a revision of that inventory that was consistent with the DSM-5 was posted. The present study evaluates the new inventory with a diverse sample of 201, 625 people from 184 countries (mainly the United States, Canada, and the United Kingdom). The 63-item inventory screens for 21 common problems and typically takes about 5 min to complete. Test scores proved to be good predictors of a variety of self-reported criterion measures, including happiness, personal and professional success, history of hospitalization, history of therapy, current participation in therapy, and employment. Females were found to have slightly more mental health problems than males, and effects were also found for education and race/ethnicity. The revised test is more accessible than the original, reducing the reading level from grade 10.2 to 6.6. It is not designed to diagnose; rather, its primary purpose is to refer people to mental health professionals for further evaluation. It can also be used in clinical settings for quick screening purposes.